Anglicismos usados en narraciones costarricenses en el volibol - González Gómez, Marjorie (Universidad de Costa Rica, 2006)
The research is based on a closed relationship between culture and language. It has an exclusively lexicographic character. It compiles and describes the lexicon used by a sample of Costa Rican sports narrators. The data were compiled fram records done fram October 1988 to April 1989. It includes volleyball historical information. The research also contains information about lexicographic works related to Anglicism in the Costa Rican Spanish.